Quantitative study on medicinal plants traded in selected herbal markets of Khyber Pakhtunkhwa, Pakistan - Shah, Sikandar; Khan, Sheharyar; Sulaiman, Sulaiman; Muhammad, Murad; Badshah, Lal; Bussmann, Rainer W; Hussain, Wahid (Ethnobotany Research and Applications, 2020)
Background: This study is the first large-scale medicinal plant survey in the herbal markets of seven Districts of Khyber Pakhtunkhwa, Pakistan. The study provides the first significant catalogue on medicinal plants trade, price patterns, routes and utilization. Methods: Based on semi structured questionnaires, interviews and group discussions with 210 informants (92.86% men and 7.14% women) and personal observations were conducted. Results: A total of 161 plant species and three species of fungi were documented. Among the plants with highest Use Value, Allium cepa were used as anthelmintic and carminative, Bergenia ciliata for bladder stones and Brassica campestris for dandruff and angina. The reported data were analyzed using various ethnobotanical indices such as Use Value (UV), Use Report (UR), Relative Frequency of Citation (RFC) and Cultural Importance Values (CIV). The most cited used plant part was seeds (22.90%), followed by fruits (19.88%), leaves (15.67%) and root (10.24%). The UV ranged from 0.18 (Seriphidium kurramnse) to 0.86 (Allium cepa, Bergenia ciliata, Brassica campestris, Carum carvi, Coriandurm sativum and Plantago major). RFC ranged from 0.976 (Allium cepa, Piper nigrum and Punica granatum) to 0.076 (Nymphaea alba and Seriphidium kurramnse). The highest mean Cultural Importance (mCI) value was recorded for Allium cepa (0.842) and lowest for Ferula assa-foetida, Terminalia chebula and Croton tiglium having each (0.083). Conclusions: The current research confirmed that Khyber Pakhtunkhwa province is an interesting area for traditional plant use that should be studied in more detail. Keywords: Quantitative study, medicinal plants, herbal markets, Khyber Pakhtunkhwa, Pakistan